1992
DOI: 10.5271/sjweh.1557
|View full text |Cite
|
Sign up to set email alerts
|

Occupationally related ultrasonic findings in carpet and floor layers' knees.

Abstract: KIVIMAKI J. Occupationally related ultrasoni c findings in carpet and floor layers' knees. Scand J Work En viron Health 1992;18:400-2. Soft-t issue changes in the anterior aspect of the knees were evaluated with ultrasonography among 96 randomly selected carpet and floor layers and 72 painters . The ultrasonography showed thickening of the prepatellar or superficial infrapatellar bursa in 49070 of the carpet and floor layers and 7% ofthe house painters. Fluid collection in the prepatellar or superficial infrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…An ultrasonographic examination of a sample of the floor and carpet layers and of the painters in Kivimaki et al's study (56,57) revealed changes in the prepatellar, the superficial, and the infrapatellar bursa in 49% of the floor and carpet layers and in 7% of the painters (56,57). Fluid accumulation was present in the prepatellar or the superficial bursa in 5.8% of the floor and carpet layers and in none of the painters.…”
Section: Bursitismentioning
confidence: 99%
“…An ultrasonographic examination of a sample of the floor and carpet layers and of the painters in Kivimaki et al's study (56,57) revealed changes in the prepatellar, the superficial, and the infrapatellar bursa in 49% of the floor and carpet layers and in 7% of the painters (56,57). Fluid accumulation was present in the prepatellar or the superficial bursa in 5.8% of the floor and carpet layers and in none of the painters.…”
Section: Bursitismentioning
confidence: 99%
“…NIOSH encouraged workers to switch to use of a power stretcher as much as possible. Knee disorders were also reviewed by Kivimaki et al (31) The researchers found considerably more knee disorders among carpet and oor layers than among painters.…”
Section: Reviewsmentioning
confidence: 99%
“…A study by Thun et al, 13) showed that carpet and floor layers experience substantially more knee morbidity than other occupational groups, and that kneeling and use of the knee kicker are risk factors, providing opportunities for prevention. Kivimaki 14) in 1992 used ultrasonography to show that soft-tissue changes in the anterior knee area were associated with knee pain among carpet and floor layers, demonstrating that kneeling work increases the risk of knee disorders and identifying radiographic changes that may be an initial sign of knee degeneration. 15 , 16) Coggon et al 17) and Cooper et al, 18) suggested that prolonged or repeated knee bending is a risk factor for knee osteoarthritis, and that risk may be higher in jobs that require knee bending and mechanical loading.…”
Section: Introductionmentioning
confidence: 99%